2022
DOI: 10.3390/vaccines10071117
|View full text |Cite
|
Sign up to set email alerts
|

Specific T-Cell Immune Response to SARS-CoV-2 Spike Protein over Time in Naïve and SARS-CoV-2 Previously Infected Subjects Vaccinated with BTN162b2

Abstract: Due to the COVID-19 pandemic, the rapid development of vaccines against SARS-CoV-2 has been promoted. BNT162b2 is a lipid-nanoparticle mRNA vaccine with 95% efficacy and is the most administered vaccine globally. Nevertheless, little is known about the cellular immune response triggered by vaccination and the immune behavior over time. Therefore, we evaluated the T-cell immune response against the SARS-CoV-2 spike protein and neutralization antibodies (nAbs) in naïve and SARS-CoV-2 previously infected subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…We therefore addressed intracellular expressions of TNF-α, IFN-γ, and, IL-2 in CD4 + and CD8 + T-cells in PLWH population and compared them to controls ( Figure 4A, B ). While the cytokine expression of S-specific IL-2, TNF-α, and IFN-γ in CD4 + T-cells did not significantly change during the study period, a declining trend was observed by T3 (Table 2), as observed earlier 29 . CD4 + or CD8 + T-cells co-expressing IFN-γ + TNF-α + IL-2 + were much more frequent in controls, however, did not reach statistical significance with either of the PLWH groups.…”
Section: Resultssupporting
confidence: 71%
“…We therefore addressed intracellular expressions of TNF-α, IFN-γ, and, IL-2 in CD4 + and CD8 + T-cells in PLWH population and compared them to controls ( Figure 4A, B ). While the cytokine expression of S-specific IL-2, TNF-α, and IFN-γ in CD4 + T-cells did not significantly change during the study period, a declining trend was observed by T3 (Table 2), as observed earlier 29 . CD4 + or CD8 + T-cells co-expressing IFN-γ + TNF-α + IL-2 + were much more frequent in controls, however, did not reach statistical significance with either of the PLWH groups.…”
Section: Resultssupporting
confidence: 71%
“…( Ndeupen et al, 2021 ) Previous studies have demonstrated a cytokine response of an increase in IP-10 and IFN-γ levels immediately after COVID-19 vaccination ( Bergamaschi et al, 2021 ). Other studies, however, found a reduction in IP-10, IFN-λ1, and IL-10 cytokine levels after vaccination against COVID-19 ( Vega-Magaña et al, 2022 ).…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, on average, studies report a preference for the female gender to produce greater antibody responses and higher B cell activity compared to men [ 23 , 42 , 43 ]. However, other authors have determined that gender does not affect the production of antibodies induced by natural infection or vaccination [ 44 , 45 ]. Numerous factors can influence immune function, including age, underlying health conditions, and lifestyle; therefore, more studies are needed in this regard, especially in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%